DILEMA PERENCANAAN PEMBANGUNAN DAN KEMAMPUAN KEUANGAN DAERAH - Arif Sofianto; Akmal Afif Fatah Yasin; Alfina Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2010)
Poverty as national problem needs an integrated plan and fiscal capacity from central with local government plan. According to that, this research are for describe some problems of developing plan and local fiscal capacity in the poverty program. This research uses study case by methode which in implemmantation of PNPM Mandiri Pedesaan and Perkotaan at Central Java Province. This research concludes that the society empowerment plan still centralize with technocratic model on central government, not enough to accommodate to local government participation, and not saw the problem of local fiscal capacity. For that result, this research needs to recomends a synchronization of local and central government plan and a sustainable formula of cost sharing.